Cultivating creative workplaces through mindfulness. Issue 1 (11th January 2019) - Byrne, Ellen Keithline; Thatchenkery, Tojo
Abstract : Purpose: The purpose of this paper is to examine how mindfulness training impacts creativity with individuals in a workgroup and propose a methodology for future research. Design/methodology/approach: The methodology developed drew on existing laboratory-based research and applied those designs in a real-world application. The sample participants were from a mid-sized real estate firm that included ten realtors and support staff, six in the treatment group and four in the comparison group. The study took place over 16 weeks where pre-test and post-test mindfulness and creativity assessments were administered. A five-week mindfulness training was conducted with the treatment group and following the post-tests with the comparison group. Findings: Results indicated that the mindfulness training positively impacted creativity in the moment and over time. There was evidence that the mindfulness training positively impacted an individual's level of attention and awareness in daily activities which is likely to influence creative outcomes in organizational settings. Research limitations/implications: This study shows that it is possible to design experimental studies in work settings and contribute to the empirical research about mindfulness despite the widely held perception about scarcity of time and lack of access to do such research. The findings also build on existing literature and address some of the gaps in current research. The most notable limitation relates to the small sample size. Practical implications: The finding affirms that even a short but consistent practice of mindfulness in organizations can lead to a measurable increase in creativity. Originality/value: This empirical study adds value to existing literature by expanding laboratory-based methodology to a practical application. One of the unique aspects of this research relates to the sample population. This research was conducted with an intact workgroup and translates the insights gained from laboratory research to a potential benefit for an organization by applying a version of this methodology to enhance its workgroup creativity.